Unveiled: tamar eaudiobook Lineage of grace series, book 1. - Rivers, Francine (Lineage of Grace, 2013)
Book one in the five-book biblical historical fiction series by the New York Times bestselling author of Redeeming Love and A Voice in the Wind . Betrayed by the men who controlled her future, she fought for her right to believe in a loving God. Meet Tamar , one of the five women in the lineage of Christ. She risked her life and her reputation to be the woman she was called to be. Her story serves as an example of how God uses our circumstances and our steps toward Him, however faltering, to fulfill His plan. Unveiled is book one in the popular Lineage of Grace series about five unlikely women who changed eternity. "Francine Rivers utilizes her expertise as master storyteller to unveil Tamar's saga, a tale of deception, betrayal, and ultimately hope." — Romantic Times